Implications of the Transfer of Workers in Cases of Corporate Reorganization - Vera Pérez, Andrea (2016)
The present article addresses the labor obligations Companies face while in the process of reorganization. In addition, it deals with the fundamental labor provisions related to the continuity principle under a conceptual and normative point of view, as a result of the transfer of employees. Finally, it explains the essential content of the agreements with relation to the transfer of personnel, as hereby previously explained.